Metaleptobasis daiglei sp. nov. from Panama (Odonata: Coenagrionidae) - Von Ellenrieder, Natalia (Zootaxa, 2022)
Metaleptobasis daiglei sp. nov. (Holotype ♂: PANAMA, Colón Province, Portobelo District, palmetto/ banana swamp, west side of Río Piedras near town of María Chiquita, 10 am (9°27’4’’N, 79°44’18’’W, 10 m), 2 June 2022, Jerrell J. Daigle leg., in FSCA) is described, figured, and distinguished from other species. Both male and female can be recognized from all congeners by the presence of a lateral pit rimmed by an external ridge between anterior and middle lobes of pronotum on each side, and the male also by the presence of a well-developed ventral spur on cercus, which supports the placement of the genus in the Teinobasini sensu De Marmels (2007).